Kajian Pendidikan Tentang Materi Pendidikan Islam Dalam Perspektif Hadits Yang Diriwayatkan Oleh Imam Muslim Atau Dikenal Dengan Hadits Jibril - Ahmad Ar Rasyid Nur Karim; Sawaluddin (Jurnal Pendidikan Tuntas, 2024)
If we studi the history of the Prophet Muhammad SAW, the deeper we study it, the more interesting it will be because all aspects have educational value. From various narrations of the Prophet Muhammad SAW, there is a hadits of the prophet narrated by Imam Muslim or better known as the Hadits of Jibril. This research aims to discuss the Hadits of Jibril which is directly related to the learning process from an educational perspective, namely educational material. Theis research is included in the library research category. The researcher recorded all general findings obtained from several literatures and sources, collected various books or texts in stages to explain each research discussion. The esidting data eas then analyzed using content analysis, then reviewing, studying and recording literature related to the research fokus. The results of the research that has been carried out show that the educational material contained in the Hadits of Jibril contains material about faith, Islamic/ Fiqh material, moral material, and material about the signs of the Day of Judgment. Key words: Educational Materials, Islam, Hadits.